Application of virtual reality technology in elderly frailty rehabilitation: a bibliometric and visual analysis - ZHOU Hui; CHEN Shuo; WENG Changshui; JIANG Tianyu; ZHANG Chi; ZHANG Li (Yixue xinzhi zazhi)
Objective To analyze the current status, research hotspots, and frontiers in elderly frailty rehabilitation with virtual reality (VR).Methods Articles or reviews related to elderly frailty rehabilitation with VR were searched from the Web of Science Core Collection and Scopus database, and the search period was from January 1996 to December 2023. To understanding the research hotspots and trends intuitively, Citespace 6.2.R3 Advanced was used for analyzing authors, countries or regions and keywords. Cluster analysis was conducted for keywords.Results A total of 653 literatures were included. Researches on elderly frailty rehabilitation with VR has been increasing steadily, reaching the peak in 2022. Among authors, Riva G from Italian was the scholar with the highest number of publications in this field. The United States was the most influential country in this field, with the highest number of publications and centrality. China ranks second in publication volume and third in centrality, making it the country with the fastest development in this field. The top-ranked keywords with high frequency were VR technology, frail population, and rehabilitation. The top-ranked keywords with high centrality were frail population, VR technology, and elderly home environment management. The top-ranked keywords with high explosive intensity were VR technology, sports performance, and elderly home environment management. The top-ranked keyword clusters were frail population, exercise rehabilitation, and patient satisfaction.Conclusion The study on elderly frailty rehabilitation with VR technology showed an upward trend. Fall prevention and motor rehabilitation training with VR technology are the hot direction of research. Further clinical research can be strengthened to provide more effective intervention methods for improving elderly frailty.